Seed science and technology - Bhanu, Chandro T. K.; International Seed Testing Association (Wageningen : International Seed Testing Association, 2009)
Vols. for 1973- include the Proceedings of the International Seed Testing Association.
Includes bibliography and index.
Chemical abstracts
English, French, or German with summaries in all three.
SERBIB/SERLOC merged record
Keywords: Seed technology -- Periodicals; Seeds -- Testing -- Periodicals; Seeds -- Periodicals; Seed technology; Seeds; Seeds -- Testing; Periodicals